Effect of heat treatment on microstructure and corrosion behavior of Mg-5Al-1Zn-1Sn magnesium alloy. (October 2021) - Ma, Yinlong; Xiong, Hongwei; Chen, Baoyi
Abstract: The effects of heat treatment on the microstructure and corrosion behavior of AZT511 magnesium alloy were investigated by microscopic analyses, immersion tests, and electrochemical measurements. The results showed that AZT511 alloy has well corrosion resistance, as the alloy showed filamentous local corrosion after immersed for 7 days. The oxide film of T4 alloy effectively prevented corrosion in the initial stage, but severe local corrosion occurred after a long-term immersion. T6 alloy had numerous local micro-galvanic corrosion originated by second phase in the initial corrosion. While a long-term immersion, it had the lowest corrosion rate as the small corrosion driving force. Highlights: AZT511 alloy showed filamentous local corrosion after immersed in the 3.5 wt% NaCl solution for 7 days. The corrosion of AZT511 alloy originated from the second phase and the elemental segregation region. Homogenization significantly improved the protection of the oxide film at the initial stage. T6 alloy has the lowest corrosion rate in long-term corrosion.